Analisis Pengalaman Pengguna dalam Redesign Website SMAN 1 Weleri Terhadap Interaksi Pengunjung - Tejo Pamungkas, Dyan Dananjaya; Muhammad Istiqlal; Louis Fernando, Vincent; Mu’arif, Rizki Alkarim; Ronggo Alit (TEKTONIK : Jurnal Ilmu Teknik, 2023)
This article analyses and redesigns the website of SMAN 1 Weleri to improve the quality and effectiveness of the school's online platform. Through an analytical and design approach, this article highlights an in-depth evaluation of the user needs, weaknesses, and strengths of the existing website. The redesign steps undertaken aim to improve the navigability, interactivity, and visual aspects of the website. The results of the redesign showed significant improvements in user experience as well as visual appeal, positively contributing to the school's image and engagement with stakeholders. In conclusion, the analysis and redesign of the school website is an important step in meeting the information needs and improving engagement between the school, students, parents and the community. Keywords: Analysis, Functionality, SMAN 1 Weleri, User Experience, Website Redesign